PEMBAHARUAN HUKUM DALAM PENYITAAN BARANG BUKTI HASIL KORUPSI - Abdul Rosyad (Jurnal Pembaharuan Hukum, 2014)
Confiscation of the assets of suspected criminals raises the pros and cons in the community. Law enforcement officers must possess prudence in conducting the investigation and prosecution as well have a strong suspicion a belief that the suspect's assets acquired in violation of the law. In confiscate whatever to do with logic, with the linking of property confiscated by the time of acquisition as well as the amount of assets that are suspected to be part of the corruption. Then the defendant in the trial also must be able to prove reverse, that property seized is not the source of corruption. Because it does not rule out someone who does have a legitimate wealth, but because of the courage and ability possessed legal knowledge may cause he was unable to explain the source of wealth is perfect. So therefore, sometimes he was found guilty of corruption.